2021
DOI: 10.3390/polym14010044
|View full text |Cite
|
Sign up to set email alerts
|

Tuning High and Low Temperature Foaming Behavior of Linear and Long-Chain Branched Polypropylene via Partial and Complete Melting

Abstract: While existing foam studies have identified processing parameters, such as high-pressure drop rate, and engineering measures, such as high melt strength, as key factors for improving foamability, there is a conspicuous absence of studies that directly relate foamability to material properties obtained from fundamental characterization. To bridge this gap, this work presents batch foaming studies on one linear and two long-chain branched polypropylene (PP) resins to investigate how foamability is affected by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…To address this issue, Kweon et al conducted a detailed study to elucidate the governing factors in PP foamability from a more fundamental perspective. The authors demonstrated that the strain hardening behavior, quantified by the extensional SHR, is the deciding factor in PP foamability at temperatures above the end melting point . This conclusion is in good agreement with the results presented in this section considering the physical reinforcement effect ion clusters have on the polymer chain network under extension.…”
Section: Results and Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…To address this issue, Kweon et al conducted a detailed study to elucidate the governing factors in PP foamability from a more fundamental perspective. The authors demonstrated that the strain hardening behavior, quantified by the extensional SHR, is the deciding factor in PP foamability at temperatures above the end melting point . This conclusion is in good agreement with the results presented in this section considering the physical reinforcement effect ion clusters have on the polymer chain network under extension.…”
Section: Results and Discussionsupporting
confidence: 87%
“…These results suggest that while some degree of strain hardening is necessary for foam expansion, a minimum level of ionic content is necessary to achieve high volume expansion and a wide foaming temperature window that are typically observed in commercial long-chain branched PP. In fact, iPP-ion2 and iPP-LCB showed almost identical expansion behavior over the temperature range 155–175 °C, despite linear PP being generally perceived as more challenging to produce highly expanded foams than long-chain branched PP . This observation further emphasizes the significance of sufficient ionic content in an inherently linear PP to allow it to exhibit a volume expansion behavior similar to the benchmark sample.…”
Section: Results and Discussionmentioning
confidence: 85%
See 3 more Smart Citations